PELAKSANAAN OTONOMI DAERAH DAN PELAYANAN PUBLIK BIDANG PENDIDIKAN DI KOTA TANGERANG - Yandri, Pitri (Faculty of Economics and Business, University of Muhammadiyah Malang, 2012)
This paper analyzes public perception of education public service before and after the implementation of regional autonomy policy. The values examined in this paper used Fisher Exact Value Test. The results of the study show that public perception of education public service in central city as well as in suburb are equal. There is no perception difference about education public service between before and after the implementation of autonomy policy. Although the public perception of public service education has been uneven, policies to improve access of the poor and people who are vulnerable to poverty to education to be important to implement. It aims to improve people's lives, especially the poor